Systematic Literature Review: Educational Curriculum in Finland - Faoziyah, Nina; Mulyono, Mulyono; Waluya, Budi (JUPE : Jurnal Pendidikan Mandala, 2025)
This study examines the Finnish curriculum through a systematic literature review to explore its strengths, challenges, and implications for education. The Finnish curriculum emphasizes a holistic approach, supporting multilingualism, broad literacy, competence development, teacher autonomy, collaboration, interdisciplinary integration, and pedagogical continuity from early childhood to higher education. Multilingualism is recognized as an educational resource that promotes linguistic diversity and social equity, while literacy encompasses critical thinking, science, health, music, soft skills, and entrepreneurship. Teachers are granted significant flexibility to design multidisciplinary learning and collaborate with local communities, although variations in practice persist. Integration of subjects and experiential learning enhances holistic understanding and critical thinking skills. Despite challenges such as language hierarchies, uneven teacher implementation, and the need for additional pedagogical support, the Finnish curriculum represents an inclusive, progressive, and future-oriented model of education. The findings provide valuable insights for policymakers and educators aiming to implement effective curriculum reforms in diverse educational contexts.